A PET sleeve for battery that does not bulge after repeated charging and discharging and a preparation method thereof

By using the appropriate amount of the PET sleeve in the battery and mixing the technical means of mixing, it solves the problem of easy drums for battery pipes in the repeated charge test test. Life has improved market competitiveness.

CN116041915BActive Publication Date: 2025-01-28CHANGYUAN CHANGTONG SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211665289.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-01-28
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

Existing PET bushings for batteries are prone to bulging during repeated charging and discharging tests, resulting in loss of insulation protection and seriously affecting the reliability and life of the battery.

Method used

PET, PCTG, EBA, PC, EBS, POE, ester exchange inhibitors, and antioxidants are mixed through an appropriate proportion to form a PET sleeve that repeatedly charges and cannot be discharged. The material is plasticized by the extruder to ensure that the material has a long life at high temperature.

Benefits of technology

The PET sleeve for the battery does not afford drums under repeated charging and discharge conditions, maintains the effect of insulation protection, extend the service life of the battery, and improves market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116041915B_ABST
    Figure CN116041915B_ABST
Patent Text Reader

Abstract

The present invention provides a PET sleeve for a battery that does not bulge during repeated charging and discharging and a preparation method thereof. The components and mass percentages of the PET sleeve for a battery that does not bulge during repeated charging and discharging are: PET 50-65%, PC 5-20%, PCTG 10-25%, EBA 5-15%, POE 2-10%, antioxidant 0.1-3%, EBS 0.1-0.5%, ester exchange inhibitor 0.1-0.5%, and the sum of the mass percentages of the components is 100%. By adopting the technical solution of the present invention, not only can the surface of the sleeve be free of particles, but the alloy material has high elasticity, hydrolysis resistance and high and low temperature resistance, and the sleeve is placed on the battery for repeated charging and discharging without bulging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a PET sleeve for a battery that does not bulge after repeated charging and discharging, and a preparation method thereof. Background Art

[0002] In recent years, cylindrical batteries have been developing in the direction of small size and high capacity. The capacity of 18650 cylindrical batteries has been upgraded from the original 1000-1500 mAh to the current 3500 mAh, and the capacity of 21700 batteries is now 5000 mAh. The larger the capacity of the battery, the larger the discharge current. During the use of the battery, the heat generated by the battery can reach above 80°C. In order to verify the reliability of the battery, power battery manufacturers will conduct charge and discharge reliability performance tests on the battery. Under normal circumstances, the test conditions are: the battery is kept at 20°C for 10 minutes → the battery is raised from 20°C to 80°C in 15 minutes during charge and discharge → 80°C is maintained for 20 minutes → the battery temperature drops from 80°C to 20°C in about 15 minutes, and the test is repeated for 600 cycles. During the test, observe the various performance indicators of the battery and the appearance of the casing. At present, during the test, it is found that the casing coated on the outside of the battery will bulge after 80-120 cycles, such as Figure 1 and Figure 2 As shown, in severe cases, the bushing may be shortened and bulged directly, causing the bushing to lose its insulating protection function.

[0003] After investigation, since this type of problem is a new type of abnormality, well-known domestic and foreign battery manufacturers such as LG, Tianpeng, Yiwei, Jiuyi and other manufacturers have reported that domestically produced PET sleeves and foreign PET sleeves such as Japan and South Korea have bulging abnormalities. Therefore, with the vigorous development of the new energy industry, the demand for power batteries in the market is increasing. Under the premise of ensuring the appearance, it is urgent to develop PET heat shrinkable sleeves for batteries that do not bulge after repeated charging and discharging, have stable performance, are safe, and have no obvious particle points. This can not only meet customer needs, but also help us improve our market competitiveness and have positive significance for promoting the battery industry to develop to a high-quality level. Summary of the invention

[0004] In view of this, the present invention discloses a PET sleeve for a battery which does not bulge during repeated charging and discharging and a preparation method thereof, in order to solve the above technical problems.

[0005] To this end, the technical solution adopted by the present invention is:

[0006] A PET sleeve for a battery which is repeatedly charged and discharged without bulging, wherein the components and their mass percentages are: 50-65% of PET (polyethylene terephthalate), 5-20% of PC (polycarbonate), 10-25% of PCTG (polyethylene terephthalate-1,4-cyclohexanedimethanol), 5-15% of EBA (ethylene butyl acrylate), 2-10% of POE (maleic anhydride grafted ethylene and octene copolymer), 0.1-3% of antioxidant, 0.1-0.5% of EBS (ethylene bisstearamide), and 0.1-0.5% of ester exchange inhibitor, wherein the mass percentages of the components are 100%, wherein the melting index of PC is 13-15.

[0007] This technical solution is adopted to blend and modify PET, PCTG, EBA, PC, EBS, POE, ester exchange inhibitor and antioxidant with appropriate proportions to prevent stress relaxation of the PET casing due to high temperature generated by the battery during repeated charge and discharge. Ultimately, it can withstand high and low temperature environments without bulging and has a longer life at high temperatures.

[0008] As a further improvement of the present invention, the Tg of the PCTG is 108-112° C. Further, the Tg of the PCTG is 110° C.

[0009] As a further improvement of the present invention, the components and mass percentages of the PET sleeve for the battery that does not bulge during repeated charging and discharging are: PET 55-65%, PC 14-20%, PCTG 10-15%, EBA 10-15%, POE 3-5%, antioxidant 0.3-0.7%, EBS 0.3-0.5%, ester exchange inhibitor 0.2-0.5%, and the sum of the mass percentages of the components is 100%.

[0010] As a further improvement of the present invention, the antioxidant comprises a primary antioxidant and an auxiliary antioxidant, the primary antioxidant is a hindered phenolic substance, and the auxiliary antioxidant is a phosphite substance. Further preferably, the antioxidant is a composite 1010 / 168 antioxidant.

[0011] As a further improvement of the present invention, the transesterification inhibitor is sodium dihydrogen phosphate (NaH2PO4) or alkyl phosphate ester.

[0012] The present invention discloses a method for preparing the above-mentioned PET sleeve for batteries which does not bulge during repeated charging and discharging, comprising the following steps:

[0013] Step S1, after the raw materials PCTG, PC, EBA and POE are uniformly mixed, extrusion granulation is performed to obtain a preliminary granulated material;

[0014] Step S2, mixing the preliminary granulated material with PET, antioxidant, EBS, and ester exchange inhibitor uniformly, and then extruding or granulating to obtain a PET sleeve for batteries that does not bulge during repeated charge and discharge.

[0015] By adopting this technical solution, PET, PCTG, EBA, PC, EBS, POE, ester exchange inhibitor and antioxidant additive are selected in appropriate proportions for physical filling and blending modification, plasticized and mixed through an extruder, and some materials with relatively low melting points are initially granulated to obtain intermediate materials that ensure the advantages of various materials. PET heat shrink tubing that does not bulge when the battery is repeatedly charged and discharged is then produced through an extruder. This can be achieved using existing equipment, and production is convenient.

[0016] Furthermore, step S1 uses a twin-screw extruder for granulation; and step S2 uses a single-screw extruder for molding.

[0017] As a further improvement of the present invention, in step S1, granulation is carried out by an extruder, and the temperatures of each zone of the extruder and the die are: first zone: 105-115°C; second zone: 250-260°C; third zone: 265-275°C; fourth zone: 265-275°C; fifth zone: 265-275°C; sixth zone: 250-260°C; seventh zone: 250-260°C; eighth zone: 250-260°C; ninth zone: 250-260°C; die: 245-255°C.

[0018] As a further improvement of the present invention, in step S2, the temperatures of the extruder and the die zones are: first zone: 270-280°C; second zone: 275-285°C; third zone: 280-290°C; fourth zone: 280-290°C; fifth zone: 275-285°C; sixth zone: 240-250°C; seventh zone: 235-245°C.

[0019] As a further improvement of the present invention, in step S1, PCTG, PC, EBA and POE are first dried at 70-80° C. for 4-6 hours.

[0020] As a further improvement of the present invention, in step S2, the preliminary granulated material, PET and EBS are first dried at 140-150° C. for 4-6 hours.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] By adopting the technical scheme of the present invention, PET, PCTG, EBA, PC, EBS, POE, ester exchange inhibitor and antioxidant additive are selected in appropriate proportions for blending and modification, and the alloy of PC and PET is toughened with POE and EBA at the same time, which can not only make the surface of the sleeve free of particles, but also make the alloy material have high elasticity, hydrolysis resistance and high and low temperature resistance, so as to achieve the effect of PET heat shrink sleeve without bulging when the battery is repeatedly charged and discharged. The formula obtained by selecting EBA material, PCTG material and PC material in appropriate proportions has high temperature resistance, and EBA also has the performance of inhibiting crystallization, so that the PET sleeve has excellent heat resistance, can maintain mechanical performance stability under double 85 conditions for 800 hours without failure, and has a longer life at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a picture of the bulging of the casing of the battery pack after charging and discharging in the prior art of the present invention.

[0024] Figure 2 This is a picture of the bulging of the casing of a single battery after charging and discharging in the prior art of the present invention. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are described in further detail below.

[0026] Example 1

[0027] A PET sleeve for batteries that does not bulge after repeated charging and discharging, the components and their mass percentages are: PET 50%, PC 5%, PCTG 25%, EBA 10%, POE 9%, antioxidant 0.4%, EBS 0.1%, ester exchange inhibitor 0.5%. Among them, the melting index of PC is 13-15.

[0028] It is prepared by the following preparation method:

[0029] Step S1, weighing PCTG, PC, and POE according to the formula (mass ratio), drying the above materials at 70-80°C for 4-6 hours, mixing them evenly, plasticizing and mixing them through a twin-screw machine, extruding and pelletizing, and obtaining preliminary granulated materials; in this step, the temperatures of the twin-screw extruder and the die head are: first zone: 105-115°C; second zone: 250-260°C; third zone: 265-275°C; fourth zone: 265-275°C; fifth zone: 265-275°C; sixth zone: 250-260°C; seventh zone: 250-260°C; eighth zone: 250-260°C; ninth zone: 250-260°C; die head: 245-255°C.

[0030] Step S2, weighing according to the formula (mass ratio), first mixing the preliminary granulated material with PET, antioxidant, EBS, and ester exchange inhibitor, plasticizing and forming through a single-screw extruder, and then towing, stretching, and winding through equipment to finally make a PET sleeve for batteries that does not bulge during repeated charging and discharging.

[0031] In this step, the temperatures of each zone of the single screw extruder and the die head are: first zone: 270-280°C; second zone: 275-285°C; third zone: 280-290°C; fourth zone: 280-290°C; fifth zone: 275-285°C; sixth zone: 240-250°C; seventh zone: 235-245°C.

[0032] Example 2

[0033] On the basis of Example 1, the components and their mass percentages of this example are: PET 60%, PC 8%, PCTG 15%, EBA 12%, POE 4%, antioxidant 0.5%, EBS 0.4%, and ester exchange inhibitor 0.1%.

[0034] The processing and preparation method is the same as Example 1.

[0035] Example 3

[0036] On the basis of Example 1, the components and their mass percentages of this example are: PET 55%, PC 14%, PCTG 12%, EBA 15%, POE 3%, antioxidant 0.3%, EBS 0.3%, and ester exchange inhibitor 0.4%.

[0037] The processing and preparation method is the same as Example 1.

[0038] Comparative Example 1

[0039] On the basis of Example 1, the components and their mass percentages of this comparative example are: PET 55%, PC 20%, PCTG 20%, EBA 0%, POE 4%, antioxidant 0.6%, EBS 0.2%, and ester exchange inhibitor 0.2%.

[0040] The preparation method is the same as that of Example 1.

[0041] Comparative Example 2

[0042] On the basis of Example 1, the components and their mass percentages of this comparative example are: PET 60%, PC 18%, PCTG 14%, EBA 5%, POE 2%, antioxidant 0%, EBS 0.5%, and ester exchange inhibitor 0.5%.

[0043] The preparation method is the same as that of Example 1.

[0044] The heat shrink tubing obtained in Examples 1 to 3 and Comparative Examples 1-2 was tested, and the main technical performance index requirements and test methods of the test are shown in Table 1. The proportions and measured performance parameters of Examples 1 to 3 and Comparative Examples 1-2 are shown in Table 2.

[0045] Table 1 Test standards and requirements

[0046]

[0047] The test method for battery bulging during charge and discharge is as follows: put the casing on the outside of the battery, randomly sample 20 batteries with the casing, and test them under the following conditions: keep the battery at 20℃ for 10 minutes → raise the battery temperature from 20℃ to 80℃ in 15 minutes during charge and discharge → keep 80℃ for 20 minutes → reduce the battery temperature from 80℃ to 20℃ in about 15 minutes, and repeat the test for 600 cycles. If there is obvious bulging on the battery surface, such as Figure 1 and Figure 2 If shown, it is unqualified.

[0048] Table 2 Examples and properties of PET heat shrink tubing that does not bulge when the battery is repeatedly charged and discharged

[0049]

[0050] From the above comparison, it can be seen that the PET heat shrink tubing using the technical solution of the present invention basically does not have the bulging phenomenon, and all performances can meet the requirements.

[0051] Comparative Example 3

[0052] This comparative example adopts the previously developed anti-battery secondary shrinkage PET heat shrink tubing, whose components and their mass percentages are: PET 50%, POK 25%, PCTG 20%, SEBS 4%, and antioxidant 1%.

[0053] The antioxidant is a composite 1010 / 168 antioxidant. The glass transition temperature of the PCTG is not less than 100°C, and the heat deformation temperature of the POK is 200-215°C.

[0054] It is prepared by the following preparation method:

[0055] Step S1, preliminary granulation: PCTG, POK, and SEBS are weighed according to the formula (mass ratio), the above materials are dried at 70-80° C. for 4-6 hours, mixed evenly, and then extruded and granulated by a twin-screw extruder to obtain preliminary granulated materials;

[0056] The following processing conditions are used for the initial granulation:

[0057] The temperatures of each zone and die head of the twin-screw extruder are as follows: Zone 1: 105-115°C; Zone 2: 215-225°C; Zone 3: 225-235°C; Zone 4: 235-245°C; Zone 5: 235-245°C; Zone 6: 230-240°C; Zone 7: 230-240°C; Zone 8: 220-230°C; Zone 9: 220-230°C; Die head: 225-235°C.

[0058] Step S2, weighing according to the formula (mass ratio), drying the preliminary granulation material and PET at 140-150°C for 4-6 hours, and mixing them evenly with the antioxidant, and then extruding them through a single screw extruder to obtain a PET heat shrinkable tube material that prevents secondary shrinkage. The temperatures of the single screw extruder and the die head are: first zone: 270-280°C; second zone: 275-285°C; third zone: 280-290°C; fourth zone: 280-290°C; fifth zone: 275-285°C; sixth zone: 240-250°C; seventh zone: 235-245°C.

[0059] Comparative Example 4

[0060] This comparative example adopts the previously developed PET sleeve for automotive capacitors resistant to cold and heat shock, and its components and their mass percentages are: PET 45%, PSU 23%, PCTG 20%, TPEE 8%, SEBS 2%, anti-aging agent 1.7%, and chain extender 0.3%.

[0061] The PET heat shrink tubing is prepared by the following steps:

[0062] (1) Preliminary granulation: PCTG, TPEE and SEBS are weighed according to the formula (mass ratio), the above materials are dried at 70-80° C. for 4-6 hours, mixed evenly, and then extruded and granulated by a twin-screw extruder to obtain preliminary granulated materials;

[0063] The following processing conditions are used for the initial granulation of raw materials:

[0064] The temperatures of each zone and die head of the twin-screw extruder are: Zone 1: 120±5℃; Zone 2: 220±5℃; Zone 3: 240±5℃; Zone 4: 245±5℃; Zone 5: 245±5℃; Zone 6: 240±5℃; Zone 7: 240±5℃; Zone 8: 235±5℃; Zone 9: 235±5℃; Die head: 230±5℃.

[0065] (2) Secondary granulation: According to the formula (mass ratio), the primary granulation material, PET, and PSU are weighed and dried at 140-150°C for 4-6 hours, and mixed with the chain extender, and then extruded and granulated by a twin-screw extruder to obtain a PET masterbatch resistant to cold and heat shock;

[0066] The temperatures of each zone and die head of the twin-screw extruder are: Zone 1: 220±5℃; Zone 2: 245±5℃; Zone 3: 260±5℃; Zone 4: 265±5℃; Zone 5: 270±5℃; Zone 6: 265±5℃; Zone 7: 265±5℃; Zone 8: 260±5℃; Zone 9: 255±5℃; Die head: 250±5℃.

[0067] (3) Extrusion and expansion molding to obtain a PET heat shrinkable tube.

[0068] The PET masterbatch resistant to cold and heat shock is mixed with an anti-aging agent, and a masterbatch can be added according to actual needs, and then extruded through a single screw extruder to obtain a PET sleeve for a vehicle-mounted capacitor resistant to cold and heat shock. The temperatures of the single screw extruder and the die head are: Zone 1: 275±5℃, Zone 2: 285±5℃, Zone 3: 290±5℃, Zone 4: 290±5℃, Zone 5: 285±5℃, Zone 6: 245±5℃, Zone 7: 240±5℃.

[0069] Comparative Example 5

[0070] The conventional PET heat shrink tubing is used, and its components and their mass percentages are: PET 51.8%, PBT 11.9%, PCTG 14.8%, TPE 2.96%, TPEE 10.4%, PA 5.9%, antioxidant 0.3%, chain extender 0.3%, fatty acid calcium 0.46%, and PC lubricant 1.48%.

[0071] The weighed PCTG, TPE, TPEE and PA are dried at 70 to 75°C for 5 to 7 hours; the dried PETG and other components are then added to a high-speed mixer and mixed evenly, and then compounded and granulated by a twin-screw extruder. The twin-screw extruder is provided with five heating zones from the feeding section to the die head. The temperatures of each zone from the feeding section are: 230±10°C, 240±15°C, 245±15°C, 250±15°C, 255±15°C; compounded granules, PET, PBT, and anti- Oxidant, chain extender, fatty acid calcium, PC lubricant are dried at 145℃-150℃ for 3 to 5 hours; finally, the dried mixed granules are added into a single screw extruder to extrude a heat shrinkable sleeve. The single screw extruder is provided with seven heating zones from the feeding section to the die section. The temperatures of the heating zones are: Zone 1: 275±5℃, Zone 2: 285±5℃, Zone 3: 290±5℃, Zone 4: 290±5℃, Zone 5: 285±5℃, Zone 6: 245±5℃, Zone 7: 240±5℃

[0072] The heat shrink tubing obtained in Example 3 and Comparative Examples 3-5 was tested, and the results are shown in Table 3.

[0073] Table 3 Comparison of PET heat shrink tube performance of Example 3 and Comparative Examples 3-5

[0074]

[0075] Through the above comparison, it can be seen that the heat shrinkable tube obtained by the embodiment of the technical solution of the present invention has better high-temperature stability and does not bulge when the battery is repeatedly charged and discharged, which can meet customer requirements.

[0076] Comparative Example 6

[0077] On the basis of Example 3, the PC used in this comparative example has a melt index of 6-8, and the other aspects are the same as those in Example 3. During extrusion, the comparative example has poor fluidity and cannot be produced.

[0078] Comparative Example 7

[0079] On the basis of Example 3, the PC used in this comparative example has a melt index of 28-30, and the other properties are the same as those in Example 3. The production is stable, and the performance comparison between the obtained sleeve and Example 3 is shown in Table 4.

[0080] Comparative Example 8

[0081] Based on Example 3, the PC melt index used in this comparative example is 48-50, and the other parts are the same as Example 3. The obtained sleeve has granular spots on the surface, and is too brittle when expanded, and often breaks. It is easy to be brittle when baked at high temperature, is not resistant to high temperature and high humidity, the material is discharged too quickly, the material is too thin, it is not easy to produce, and it is difficult to form. The thickness is difficult to control. The performance comparison between this comparative example and Example 3 is shown in Table 4.

[0082] Table 4 Performance comparison of Example 3 and Comparative Examples 8-9

[0083]

[0084] Through the above comparison, it can be seen that the melt index of PC will affect the performance of PET tube. PC with MI of 13-15 has better mechanical properties such as elongation at break, tensile strength, lateral shrinkage, longitudinal shrinkage, etc. It has better high temperature and high humidity performance, does not bulge when the battery is repeatedly charged and discharged, and has fewer obvious particle points, which can meet customer requirements.

[0085] Comparative Example 10

[0086] On the basis of Example 3, this comparative example uses PSU to replace PC, and the rest is the same as Example 3. The production is stable, and the particle points on the appearance of the obtained casing reach 4762ppm. There are too many particle points, which does not meet the requirements of battery customers.

[0087] Comparative Example 11

[0088] On the basis of Example 3, this comparative example uses PCTG with a Tg of 110° C. to replace PC, and the other aspects are the same as Example 3. The discharge is unstable during extrusion and the sleeve product cannot be produced.

[0089] Comparative Example 12

[0090] On the basis of Example 3, this comparative example uses HDPE to replace PC, and the other aspects are the same as Example 3. The production is stable, and the stress relaxation of the obtained sleeve is serious, resulting in a serious decrease in the lateral shrinkage rate after the product is placed for 24 hours; the appearance is not good, the folding stress is white, resulting in an unqualified appearance, and the basic appearance requirements of the PET sleeve cannot be met.

[0091] Through the above comparison, it can be seen that using PSU, HDPE and high Tg PCTG to replace PC cannot meet the requirements.

[0092] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A PET casing for batteries that does not bulge after repeated charging and discharging, characterized in that: Its components and their mass percentages are: PET 55-65%, PC 14-20%, PCTG 10-15%, EBA 10-15%, POE 3-5%, antioxidant 0.3-0.7%, EBS 0.3-0.5%, ester exchange inhibitor 0.2-0.5%, the sum of the mass percentages of each component is 100%, wherein the melt index of PC is 13-15; the ester exchange inhibitor is sodium dihydrogen phosphate or alkyl phosphate ester.

2. The PET casing for batteries that does not bulge after repeated charging and discharging according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and an auxiliary antioxidant, wherein the primary antioxidant is a hindered phenolic substance, and the auxiliary antioxidant is a phosphite substance.

3. The method for preparing a PET sleeve for a battery that does not bulge after repeated charge and discharge according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1, after the raw materials PCTG, PC, EBA and POE are uniformly mixed, extrusion granulation is performed to obtain a preliminary granulated material; Step S2, mixing the preliminary granulated material with PET, antioxidant, EBS, and ester exchange inhibitor uniformly, and then extruding or granulating to obtain a PET sleeve for batteries that does not bulge during repeated charge and discharge.

4. The method for preparing the PET sleeve for battery with repeated charge and discharge without bulging according to claim 3, characterized in that: In step S1, granulation is performed by an extruder, and the temperature of each zone of the extruder and the die head is: first zone: 105-115°C; Second zone: 250~260℃; third zone: 265~275℃; fourth zone: 265~275℃; fifth zone: 265~275℃; sixth zone: 250~260℃; seventh zone: 250~260℃℃; eighth zone: 250~260℃℃; ninth zone: 250~260℃℃; die head: 245~255℃.

5. The method for preparing the PET sleeve for batteries that does not bulge after repeated charge and discharge according to claim 4, characterized in that: In step S2, the temperatures of the extruder and die zones are: first zone: 270-280°C; Zone 2: 275~285℃; The third zone: 280~290℃; the fourth zone: 280~290℃; fifth Zone 1: 275~285℃; Zone 6: 240~250℃; Zone 7: 235~245℃.

6. The method for preparing a PET sleeve for a battery that does not bulge after repeated charging and discharging according to claim 5, characterized in that: In step S1, PCTG, PC, EBA and POE are first dried at 70-80° C. for 4-6 hours.

7. The method for preparing a PET sleeve for batteries that does not bulge after repeated charging and discharging according to claim 6, characterized in that: In step S2, the preliminary granulated material, PET and EBS are first dried at 140-150° C. for 4-6 hours.

Citation Information

Patent Citations

  • Method for preparing heat shrinkable socket pipe

    CN101049729A

  • Preparation method of composite material with high-temperature-resisting and flame-retarding properties and material

    CN108384206A

  • Smooth-appearance PET (Polyethylene Terephthalate) heat-shrinkable sleeve for battery and preparation method thereof

    CN114806105A